Effect of resveratrol on metabolic and cardiovascular function in male and female adult offspring exposed to prenatal hypoxia and a high‐fat diet. (4th November 2015) - Shah, Amin; Reyes, Laura M.; Morton, Jude S.; Fung, David; Schneider, Jillian; Davidge, Sandra T.
Abstract : Key points: Prenatal hypoxia, a common outcome of many pregnancy complications, predisposes offspring to chronic diseases in later life. We investigated the effect of prenatal hypoxia, on a background of a high‐fat diet, on metabolic and cardiac function in adult male and female rat offspring. We also examined the therapeutic role of resveratrol supplementation in preventing metabolic and cardiac dysfunction. Prenatal hypoxia impaired both metabolic and cardiac function in male and only cardiac function in female rat offspring. We also observed that male rat offspring were more susceptible to metabolic and cardiac dysfunction as compared with their female counterparts; this provides evidence of sexual dichotomy in the fetal programming of diseases due to prenatal hypoxia. Resveratrol supplementation in the diet improved metabolic and cardiac function independent of sex; this provides evidence of a possible therapeutic role of resveratrol in susceptible male and female rat offspring exposed to prenatal hypoxia. Abstract: Prenatal hypoxia, a common outcome of pregnancy complications, predisposes offspring to the development of metabolic and cardiovascular disorders in later life. We have previously observed that resveratrol improved cardiovascular and metabolic health in adult male rat offspring exposed to prenatal hypoxia and a postnatal high‐fat (HF) diet; however, the effects of resveratrol in female rat offspring are not known. Our aim was to identify the mechanism(s) by which resveratrol may prevent metabolic and cardiac dysfunction in both male and female rat offspring exposed to prenatal hypoxia and a postnatal HF diet. Offspring that experienced normoxia or hypoxia in utero were fed a HF diet or a HF diet supplemented with resveratrol for 9 weeks following weaning. Body composition, metabolic function, in vivo cardiac function and ex vivo cardiac susceptibility to ischaemia–reperfusion (I/R) injury were assessed at 12 weeks of age. Prenatal hypoxia impaired metabolic function in male, but not female, rat offspring fed a HF diet and this was improved by resveratrol supplementation. Prenatal hypoxia also led to reduced recovery from cardiac I/R injury in male, and to a lesser extent in female, rat offspring fed a HF diet. Indices of cardiac oxidative stress after I/R were enhanced in both male and female rat offspring exposed to prenatal hypoxia. Resveratrol improved cardiac recovery from I/R injury and attenuated superoxide levels in both male and female rat offspring. In conclusion, prenatal hypoxia impaired metabolic and cardiac function in a sex‐specific manner. Resveratrol supplementation may improve metabolic and cardiovascular health in adult male and female rat offspring exposed to prenatal hypoxia. Key points: Prenatal hypoxia, a common outcome of many pregnancy complications, predisposes offspring to chronic diseases in later life. We investigated the effect of prenatal hypoxia, on a background of a high‐fat diet, on metabolic and cardiac function in adult male and female rat offspring. We also examined the therapeutic role of resveratrol supplementation in preventing metabolic and cardiac dysfunction. Prenatal hypoxia impaired both metabolic and cardiac function in male and only cardiac function in female rat offspring. We also observed that male rat offspring were more susceptible to metabolic and cardiac dysfunction as compared with their female counterparts; this provides evidence of sexual dichotomy in the fetal programming of diseases due to prenatal hypoxia. Resveratrol supplementation in the diet improved metabolic and cardiac function independent of sex; this provides evidence of a possible therapeutic role of resveratrol in susceptible male and female rat offspring exposed to prenatal hypoxia.